Analisis Kritis Isu Kesetaraan Akses Pendidikan dalam Kompetisi Negara ASEAN (Studi Kasus di Indonesia, Malaysia dan Brunei Darussalam) - Sukari, Sukari; Nurachman, Azhar (Lembaga Yasin AlSys, 2025)
This research analyzes the equality of access to education in three ASEAN countries: Indonesia, Malaysia, and Brunei Darussalam. Each country faces different challenges and adopts distinct strategies to achieve equitable access to education for all its citizens. Brunei Darussalam stands out with its comprehensive free education system, well-distributed infrastructure, and strong support for inclusive education and technology. Malaysia has made progress with free education and financial assistance but still struggles with digital divides and infrastructure gaps in remote areas. Indonesia faces the greatest challenges due to its vast geography and regional disparities, despite implementing various programs such as the 12-Year Compulsory Education Program and the Smart Indonesia Card (KIP). Overall, Brunei excels in implementing more equitable education policies, while Malaysia and Indonesia still need improvements in infrastructure distribution, access to technology, and support for students with special needs.